2008
DOI: 10.1074/jbc.m708134200
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Tat System from a Gram-positive Organism

Abstract: The Tat system transports folded proteins across bacterial and thylakoid membranes. In Gram-negative organisms, a TatABC substrate-binding complex and separate TatA complex are believed to coalesce to form an active translocon, with all three subunits essential for translocation. Most Gram-positive organisms lack a tatB gene, indicating major differences in organization and possible differences in mode of action. Here, we have studied Tat complexes encoded by the tatAdCd genes of Bacillus subtilis. Expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Another feature to be addressed here is the presence of Sec-independent Tat pathway genes for folded proteins’ secretion. Twin-arginine translocase subunits A and C are presented in PM4 and S5 genomes, which may be functional in an analogy with a Gram-positive bacterial Tat system, known to work without additional TatB protein33.…”
Section: Resultsmentioning
confidence: 99%
“…Another feature to be addressed here is the presence of Sec-independent Tat pathway genes for folded proteins’ secretion. Twin-arginine translocase subunits A and C are presented in PM4 and S5 genomes, which may be functional in an analogy with a Gram-positive bacterial Tat system, known to work without additional TatB protein33.…”
Section: Resultsmentioning
confidence: 99%
“…To standardize nomenclature between organisms, we will refer to this complex as Tat(A)BC complex. In Gram-positive bacteria, the sole TatA and TatC subunits can also be recovered from separate TatAC and TatA complexes [87]. Despite the fact that Tat subunits are consistently recovered from these Tat(A)BC and TatA complexes, doubt has been cast on the functional relevance of those isolatable structures.…”
Section: The Components Of Tat Translocases (A) Homologues Of Tatc Anmentioning
confidence: 99%
“…Considering that components from other bacterial TAT systems can work efficiently in E. coli (43,44), EfeB and TatCA were coexpressed in E. coli dEAD. EfeB could be observed in the supernatant of dEAD/ efeB-TatCA by SDS-PAGE, which suggested that a large amount of EfeB was exported.…”
Section: Discussionmentioning
confidence: 99%